Relation of Risk Factors and Clinicopathological Features in Sinonasal Malignancy (Bangladesh Journal of Otorhinolaryngology, 2026)
Background: Sinonasal carcinoma is a rare but aggressive malignancy arising from the nasal cavity and paranasal sinuses. Delayed diagnosis due to nonspecific symptoms often leads to advanced-stage presentation. In Bangladesh, occupational exposure among workers in furniture industries, sawmills, textile industries, and chemical factories may increase the burden of sinonasal malignancies. However, there is limited published data regarding risk factors and clinicopathological patterns in the Bangladeshi population. The present study aims to evaluate the risk factors and clinicopathological correlations of sinonasal carcinoma in Bangladesh and compare findings with international literature.Objective: To evaluate the risk factors and clinicopathological correlations of sinonasal carcinoma among Bangladeshi patients.Methods: A cross-sectional observational study was conducted in the Department of Otolaryngology–Head and Neck Surgery at Bangladesh Medical University and Ahsania Mission Cancer & General Hospital in Bangladesh from January 2022 to May 2026. Eighty patients with histopathologically confirmed sinonasal carcinoma were included. Demographic characteristics, risk factors, clinical presentations, tumor sites, histopathological findings, and staging were analyzed.Results: The mean age of the patients was 54.6 ± 11.8 years, with the highest incidence observed in the 51–60-year age group (35%). Males constituted 68.8% of the cases. Tobacco use was identified in 62.5% of patients, occupational wood dust exposure in37.5%, industrial chemical exposure in 28.8%, and smoking in 56.3%. Nasal obstruction (85%), epistaxis (72.5%), facial swelling (48.8%), and proptosis (22.5%) were the common presenting symptoms. The maxillary sinus was the most frequently involved site (46.3%), followed by the nasal cavity (31.3%). Squamous cell carcinoma accounted for 62.5% of cases, followed by adenocarcinoma (15%), sinonasal undifferentiated carcinoma (10%), adenoid cystic carcinoma (7.5%), and others (5%). Advanced-stage disease (Stage III and IV) was present in 71.3% of patients. Significant associations were found between occupational exposure and adenocarcinoma (p